Težave na primarni ravni pri oskrbi z ustreznimi ortozami in medicinskimi pripomočki za gibanje - Karapandža, Jurij (Rehabilitacija (Ljubljana), 2019)
Efficient health care systems aim to provide a suitable amount of services at the primary level, including provision of orthoses and mobility aids. But it is often difficult to draw a distinct line between the primary and the secondary level of health care. Twenty-one per cent of orthoses were prescribed at the primary level in Slovenia in 2017. The majority of those orthoses were of only three types: lower-back braces, peroneal orthosis and ankle orthosis. In the author's view, such limited prescription of orthoses could be attributed to narrowly defined medical criteria, incomplete List of Medical Devices, the fact that specialists are not authorised to prescribe medical aids with slight alterations for individual needs or simple individually-designed orthoses, low price standards, unclearly defined standard "the cheapest appropriate medical aid that is still functional", and the shortage of certified orthotists at the primary health care level as well as among orthotics suppliers. The instructions that are given to manufacturers of individually designed orthopaedic shoes by medical specialists often lack specific information on characteristics and corrections that the orthopaedic shoes should have. That raises the question whether all the designated specialists are sufficiently qualified for prescribing appropriate orthopaedic shoes. The author also points out that the rate of prescribed powered wheelchairs is very low at the primary level. Another difficulty that the patients face is that tilting wheelchairs can be prescribed only by a few specialists who have been given special authorisation by the Health Insurance Institute of Slovenia, and none of them works at the primary health care level.
Keywords: medicinski pripomočki za gibanje; mobility aids; orthopedic shoes; Orthotic Devices; orthotic prescription; ortopedski čevlji; ortoze; othroses; predpisovanje ortoz; primarno zdravstvo; primary level